Comprehensive Study on Effectiveness of Automatic Flood Door Barrier - Muhammad Muzammil Mohd Khairi; Yusfandi, Nor Asikin; Muhammad Ali Izuan Dzulkeflee; Khairi Supar (Multidisciplinary Applied Research and Innovation, 2025)
Flood barriers, encompassing structures such as walls, levees,dams, or gates, play a vital role in safeguarding against the detrimental impact of escalating water levels. These barriers, made of materials such as concrete or steel, are crucial for protecting residential, commercial, and critical infrastructure sectors. Their efficacy depends on variables such as the flood event’s configuration, location, and scale. The objective of this project is to create a practical and user-friendly prototype of an automatic flood door barrier, mostly constructed from acrylic. Additionally, the project aims to assess the effectiveness of the automatic flood door barrier in with standing floods in residential areas. The project’s to ascertain the optimal application of acrylic in the fabrication of an automatic flood door barrier, with the ultimate aim of alleviating the Ultimately, the properties of acrylic render it a desirable substance for inhibiting the ingress or seepage of water into the dwelling. Further studies should focus on investigating the material effects of flood door barriers to fully comprehend the benefits and potential of acrylic, which distinguishes itself from other materials.